2017
DOI: 10.1080/09658211.2016.1270967
|View full text |Cite
|
Sign up to set email alerts
|

Time manages interference in visual short-term memory

Abstract: Emerging evidence suggests that age-related declines in memory may reflect a failure in pattern separation, a process that is believed to reduce the encoding overlap between similar stimulus representations during memory encoding. Indeed, behavioural pattern separation may be indexed by a visual continuous recognition task in which items are presented in sequence and observers report for each whether it is novel, previously viewed (old), or whether it shares features with a previously viewed item (similar). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…The distractor was placed half way into the retention interval and this arrangement allowed ample time to consolidate the representation, increasing its resilience to distraction. Smith, McKeown, and Bunce (2017) have shown that extending the interval between successive images in a visual recognition task improves performance and Ricker and Cowan (2014) argue that forgetting is greatly reduced when there is sufficient time to consolidate the items into memory.…”
Section: Discussionmentioning
confidence: 99%
“…The distractor was placed half way into the retention interval and this arrangement allowed ample time to consolidate the representation, increasing its resilience to distraction. Smith, McKeown, and Bunce (2017) have shown that extending the interval between successive images in a visual recognition task improves performance and Ricker and Cowan (2014) argue that forgetting is greatly reduced when there is sufficient time to consolidate the items into memory.…”
Section: Discussionmentioning
confidence: 99%